Glucose and lactate in umbilical artery serum in term neonates at high altitude - Villamonte, Wilfredo (2014)
Objectives: To determine umbilical artery glucose and lactate in newborns at term, at 3 400 m above sea level. Design: Prospective, cross-sectional study. Institution: Hospital Nacional Adolfo Guevara Velazco, EsSalud, Cusco, Peru. Participants: Term neonates, at 3 400 m above sea level. Methods: From August 2010 through December 2011 umbilical artery serum was obtained from 240 term neonates born at the Hospital. Mean values and 5th and 95th centiles of glucose and lactate of newborns’ umbilical artery were determined. Main outcome measures: Glucose and lactate values of newborns’ umbilical artery. Results: Pregnant women average age was 31 years, hemoglobin 13.9 g/dL and one previous child. Neonate average weight was 3 240 g, height 49.4 cm, weight status 2.7, umbilical artery hematocrit 48% and placental weight 666.4 g. Glucose was 4.6 mmol/L and lactate 4.4 mmol/L. Conclusions: Mean term neonates glucose and lactate at 3 400 m above sea level were respectively 4.6 and 4.4 mmol/L.